A study on palatal rugae pattern among UPCD students - Lansang, Faye Angeli
#aThe palatine rugae pattern, just like fingerprints, is established as unique to every individual. It is said that ethnic differences in these patterns exist. Various foreign researches suggested that the palatal rugae pattern can be used as human identification, however, this method have yet to be established in the Philippines since there are no studies done as of present. For this reason, the study aims to determine the palatal rugae pattern among UPCD students. In effect, the determination of a unique pattern among filipinos may become useful in the field of Forensic Dentistry. Methods: A total of 63 dental casts were made from the subjects. The rugae patterns in each cast was classified using the Lysell classification to identify the unique features existing on the rugae patterns. The characteristics observed were number, length, shape, direction, and unification of rugae. The collected data were statistically processed using the Stata 10.0 software at 95% confidence interval. Results: The palatal rugae pattern of the subjects are commonly comprised of primary (60%), curved (37%), forwardly directed (49%), and diverging types (65%) of rugae. The average number was 16.135, being slightly higher in female than male. Two-way ANOVA analysis showed significant differences between the left and right side of the palate on the circular, forwardly directed, and backwardly directed types of rugae. However, no significant difference was shown between the sexes. Conclusion: It can therefore be concluded that there are unifying features present on the rugae pattern among the UPCD students. However, the palatal rugae of the sample population did not show significant difference on both sexes.